Respuestas
Respuesta dada por:
0
➊
8x - 34 = 3x + 46
8x - 3x = 46 + 34
5x = 80
x = 16
➋
4x + 5x = 11x -40
9x = 11x - 40
40 = 11x - 9x
40 = 2x
20 = x
➌
7x+ 3x = 45 - 5x
10x = 45 - 5x
15x = 45
x = 3
➍
12x - 45 = 8x + 3x - 2x
12x - 8x - 3x + 2x = 45
3x = 45
x = 15
➎
12x - 27 = 4x + 5
12x - 4x = 27 + 5
8x = 32
x= 4
➏
4x - 25 = 20 - 5x
9x = 45
x = 5
8x - 34 = 3x + 46
8x - 3x = 46 + 34
5x = 80
x = 16
➋
4x + 5x = 11x -40
9x = 11x - 40
40 = 11x - 9x
40 = 2x
20 = x
➌
7x+ 3x = 45 - 5x
10x = 45 - 5x
15x = 45
x = 3
➍
12x - 45 = 8x + 3x - 2x
12x - 8x - 3x + 2x = 45
3x = 45
x = 15
➎
12x - 27 = 4x + 5
12x - 4x = 27 + 5
8x = 32
x= 4
➏
4x - 25 = 20 - 5x
9x = 45
x = 5
Respuesta dada por:
2
2(3x - 5) - 2x = 3x - ( 2x - 3 )
Resultado: x = 13/3
x-4/3 - 2x-1/6 = 2( -x + 53/12 )
Resultado: x= 60/12 = 5
2x(3x-5) - x + 3 = 6(x2 - 2x + 5)
Resultado: x= 72
(5x-1/2)(x+1/3) - 1-2x/2 = x/3 - 1-5x2/6
Resultado: x = 3/8
(x-1/2) - 3(x+1) = 2(x+1/4)
Resultado: x= 16/-16= -1
3(2x-5)+8x-6= x/2 - (5x+3)
Resultado: x=36/37
4(x-3) + x/8 = -(x -4) + 1
Resultado: x=34/11
x/3 - 2x-1/6 = 2(-x + 53/12)
Resultado: x= 55/24
x-3/2 - x-1/8 = 1/8
Resultado: x= 14/3
3(x+3)/5 - x/15 = -69/15
Resultado: x= -96/8 = -12
Resultado: x = 13/3
x-4/3 - 2x-1/6 = 2( -x + 53/12 )
Resultado: x= 60/12 = 5
2x(3x-5) - x + 3 = 6(x2 - 2x + 5)
Resultado: x= 72
(5x-1/2)(x+1/3) - 1-2x/2 = x/3 - 1-5x2/6
Resultado: x = 3/8
(x-1/2) - 3(x+1) = 2(x+1/4)
Resultado: x= 16/-16= -1
3(2x-5)+8x-6= x/2 - (5x+3)
Resultado: x=36/37
4(x-3) + x/8 = -(x -4) + 1
Resultado: x=34/11
x/3 - 2x-1/6 = 2(-x + 53/12)
Resultado: x= 55/24
x-3/2 - x-1/8 = 1/8
Resultado: x= 14/3
3(x+3)/5 - x/15 = -69/15
Resultado: x= -96/8 = -12
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años